Collaborative Benefits and Coordination Costs: Learning and Capability Development in Science - VURAL, M. Onal (Institutional Knowledge at Singapore Management University, 2013)
We examine the effects of team structure and experience on the impact of inventions produced by scientific teams. Whereas multidisciplinary, collaborative teams have become the norm in scientific production, there are coordination costs commensurate with managing such teams. We use patent citation analysis to examine the effect of prior collaboration and patenting experience on invention impact of 282 patents granted in human embryonic stem cell (hESC) research from 1998 to 2010. Our results reveal that team experience outside the domain may be detrimental to project performance in a setting where the underlying knowledge changes. In stem cell science, we show that interdepartmental collaboration has a negative effect on invention impact. Scientific proximity between members of the team has a curvilinear relationship, suggesting that teams consisting of members with moderate proximity get the highest impact. We elaborate on these findings for theories of collaboration and coordination and its implications for radical scientific discoveries.